Is Carpal Tunnel Release Necessary in High-Energy Distal Fractures of the Radius? - Kazez, Muhammed; Agar, Anil; Key, Sefa; Ayas, Orhan; Gurbuz, Mustafa Umit (Springernature, 2024)
Purpose This study aimed to compare the clinical outcomes of patients who underwent volar plate osteosynthesis for high-energy distal radius fracture (DRFx) and carpal tunnel release (CTR) for acute or subacute carpal tunnel syndrome (CTS) with patients who did not undergo CTR. Methods This study is a retrospective evaluation of all high-energy DRFx treated with volar plate osteosynthesis in a regional hospital between January 2021 and January 2023. All adult patients (>= 18 years) who underwent open reduction and internal fixation were included in the study after obtaining approval from the internal review board of our institution. Only patients who underwent plate osteosynthesis of the volar aspect through a modified Henry incision and patients who underwent CTR through a classic separate incision were included in the study. Clinical results include hand dynamometry, visual analog scale (VAS) scores, and physical examination findings of patients who underwent volar plate osteosynthesis because of high-energy DRFx and CTR due to CTS in the acute and subacute periods were retrospectively examined. Results Among the patients who underwent volar plate osteosynthesis because of high-energy DRFx, no statistically significant difference was detected between the hand grip strength and VAS scores of patients who underwent CTR because of acute CTS and subacute CTS at the sixth postoperative week (p>0.05). Conclusion Prophylactic CTR may be performed in the same session in selected cases, such as DRFx caused by a highenergy injury, to establish a scale for DRFx at a high risk of CTS and avoid delays in treatment. CTR for transient CTS detected in the subacute period during outpatient follow-up does not improve clinical outcomes.
Keywords: plate osteosynthesis; radius distal fracture; high energy; carpal tunnel syndrome; carpal tunnel release